2005
DOI: 10.2174/1567205052772713
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances on Different Kinases Involved in Tau Phosphorylation, and Implications in Alzheimers Disease and Tauopathies

Abstract: Hyperphosphorylation and accumulation of tau in neurons (and glial cells) is one the main pathologic hallmarks in Alzheimer's disease (AD) and other tauopathies, including Pick's disease (PiD), progressive supranuclear palsy, corticobasal degeneration, argyrophilic grain disease and familial frontotemporal dementia and parkinsonism linked to chromosome 17 due to mutations in the tau gene (FTDP-17-tau). Hyperphosphorylation of tau is regulated by several kinases that phosphorylate specific sites of tau in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
190
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(198 citation statements)
references
References 135 publications
(173 reference statements)
8
190
0
Order By: Relevance
“…It was also reported previously that proteasome inhibition by MG-132, a reversible proteasome inhibitor, stabilizes tau inclusions in oligodendroglial cells treated with okadaic acid [34]. As a more obvious accumulation of the hyperphosphorylated tau was observed in HEK293/441 cells during protea- some inhibition, we measured the activity of GSK-3, a crucial tau kinase [5]. We observed that the activity of GSK-3 was significantly increased after treatment of the cells with lactacystin.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It was also reported previously that proteasome inhibition by MG-132, a reversible proteasome inhibitor, stabilizes tau inclusions in oligodendroglial cells treated with okadaic acid [34]. As a more obvious accumulation of the hyperphosphorylated tau was observed in HEK293/441 cells during protea- some inhibition, we measured the activity of GSK-3, a crucial tau kinase [5]. We observed that the activity of GSK-3 was significantly increased after treatment of the cells with lactacystin.…”
Section: Discussionsupporting
confidence: 51%
“…Among various kinases and phosphatases, glycogen synthase kinase-3 (GSK-3) and protein phosphatase-2A (PP-2A) are, respectively, the crucial kinase and phosphatase for the ADlike tau hyperphosphorylation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested mitogen-activated protein kinases (MAPKs) as key regulators of the formation of plaques and tau hyperphosphorylation in AD (147). MAPKs pathways transduce intracellular signaling to increase expression of different proteins; dysregulation of MAPK-dependent pathways suggests a systematic disorder of protein translation regulation in MCI brains.…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 99%
“…Moreover, GSK-3b has been shown to regulate cyclin D1 proteolysis and subcellular localization in mouse fibroblasts (Diehl et al 1998). GSK-3 has also been implicated in Alzheimer's disease (Ferrer et al 2005). In the present study, we have investigated how GSK-3a and GSK-3b are regulated by soluble KL in cultured growing mouse oocytes, and suggest that GSK-3 may play a role in oocyte growth and early follicular development.…”
Section: Introductionmentioning
confidence: 84%